Development of trade and economic cooperation between Kazakhstan and China - А.Ы. Ыкласова (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
Kazakhstan and China have a high demand for economic development. Strengthening large-scale and mutually beneficial trade and economic cooperation with the People’s Republic of China is one of the main directions of the overall strategy for the development of foreign economic relations of the Republic of Kazakhstan. Bilateral relations between Kazakhstan and China have gone through several stages. Both sides are developing trade and economic cooperation with each other through trade, investment, energy, and so on. A wide range of areas of cooperation between Kazakhstan and China carry out multilateral trade and economic cooperation. Today, China is one of the main trade and economic partners of Kazakhstan, covering several areas of cooperation between the two countries in the modernization of the Silk Road. This scientific research aims some of the strategic aspects of the two countries and the potential economic consequences. In addition, the study analyzes the project for the implementation of the Silk Road Economic Belt using the economic development of the Khorgos SEZ (Special Economic Zone).